1986
DOI: 10.1149/1.2108421
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Via‐Filling Technology with Electroless Plating Method

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…At high overpotential, the surface concentration of X becomes zero and a limiting current density il is obtained i~ = nFAD ~ [1] in which n is the number of transferred electrons, F the Faraday constant, A the surface area, Cb the bulk concentration, D the diffusion coefficient, and 8 the thickness of the diffusion layer. For a small spatially isolated circular electrode (microdisk electrode), one can show that, under steady-state conditions, the diffusion-limited current density due to nonlinear diffusion/~1 is equal to ~3 inl = 4nFAD (~r) [2] By comparing Eq. 1 and 2 it is clear that nonlinear diffusion can be neglected fully for large substrates.…”
Section: Mass Transport In the Liquid Phasementioning
confidence: 99%
“…At high overpotential, the surface concentration of X becomes zero and a limiting current density il is obtained i~ = nFAD ~ [1] in which n is the number of transferred electrons, F the Faraday constant, A the surface area, Cb the bulk concentration, D the diffusion coefficient, and 8 the thickness of the diffusion layer. For a small spatially isolated circular electrode (microdisk electrode), one can show that, under steady-state conditions, the diffusion-limited current density due to nonlinear diffusion/~1 is equal to ~3 inl = 4nFAD (~r) [2] By comparing Eq. 1 and 2 it is clear that nonlinear diffusion can be neglected fully for large substrates.…”
Section: Mass Transport In the Liquid Phasementioning
confidence: 99%
“…The electroless deposition of metals and alloys can be considered an established industrial practice. Apart from its well-known applications in circuit technology 1 and for the production of corrosion and wear-resistant coatings, 2,3 this technique has also attracted interest as a preparation method for new electrocatalytic electrode materials. 4,5 Electroless Ni±P alloy is a typical metal±metalloid binary system and has been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%
“…23,24 However, attempts to form micropatterns by electroless deposition using dimethylamineborane ͑DMAB͒ as the reducing agent showed that the film deposition occurred not only on the catalytic surface but also on the photoresist. [26][27][28] The behavior of the electroless deposition system is said to depend on the nature of the catalyst 29,30 and the substrate geometry. 31 In our previous study, the selectivity of electroless deposition from the DMAB bath was improved by using bath agitation and incorporating organic additives in the plating bath.…”
mentioning
confidence: 99%